Therapeutics for the treatment of coronavirus disease 2019 in children and adolescents - Soo-Han Choi; Jae Hong Choi; Ki Wook Yun (The Korean Pediatric Society, 2022)
Coronavirus disease 2019 (COVID-19) is a mild to moderate respiratory illness in most children and adolescents, but a small proportion develop severe or critical illness. Although pediatric clinical trials for the treatment of COVID-19 are sparse, there are some available drugs for children and adolescents with severe COVID-19. This review summarizes clinical data focusing on antiviral agents and immunomodulators for COVID-19 treatment. Additionally, the current recommendations for therapeutics for children and adolescents with COVID-19 are discussed. Remdesivir is suggested for pediatric patients with COVID-19 in the following cases: children and adolescents with severe COVID-19 who need supplemental oxygen without mechanical ventilation; adolescents aged ≥12 years and weight of at least 40 kg with COVID-19 who do not require supplemental oxygen and are within 7 days of symptom onset and are at high risk of progression to severe illness. Nirmatrelvir/ritonavir is considered for adolescents aged ≥12 years and weighing at least 40 kg who do not require supplemental oxygen and are within 5 days of symptom onset and are at high risk of progression to severe disease. Corticosteroids are not recommended in children and adolescents with mild to moderate COVID-19. Corticosteroids are recommended in children and adolescents with severe to critical COVID-19.